Intra-articular Administration of Allogeneic Adipose Derived MSCs Reduces Pain and Lameness in Dogs With Hip Osteoarthritis: A Double Blinded, Randomized, Placebo Controlled Pilot Study - Maki, Chad B.; Beck, Anthony; Wallis, Chan-Benami Cheuk Chi; Choo, Justin; Ramos, Thomas; Tong, Raymond; Borjesson, Dori L.; Izadyar, Fariborz (Frontiers in Veterinary Science, 2020)
This study was conducted to investigate the therapeutic effect of allogeneic adipose-derived MSCs on dogs with hip osteoarthritis (OA). Twenty dogs with bilateral osteoarthritis of the coxofemoral (hip) joint, diagnosed by a veterinarian through physical examination and radiographs were randomly allocated into four groups. Group 1 served as a placebo control and were injected with 0.9% sodium chloride (saline) (n=4). Group 2 were injected with a single dose of 5 million MSCs (n=5). Group 3 received a single dose of 25 million MSCs (n=6) and Group 4 received a single dose of 50 million MSCs (n=5). Intra-articular administration of allogeneic MSCs into multiple joints did not result in any serious adverse events. The average lameness score of the dogs in the placebo control group (-0.31) did not show improvement after 90 days of intra-articular saline administration. However, the average lameness score of the all MSC-treated dogs was improved 2.11 grade at this time point (P<0.001). Overall, sixty five percent (65%) of the dogs that received various doses of MSCs showed improvement in lameness scores 90 days after intra-articular MSC administration. Our results showed that intra-articular administration of allogeneic adipose derived MSCs was well tolerated and improved lameness scores and reduced pain in dogs associated with hip OA. All doses of MSCs were effective. Subsequent studies with more animals per group are needed to make a conclusion about the dose response. The improved lameness effect was present up to 90 days post-injection. Serum interleukin 10 was increased in a majority of the dogs that received MSCs and that also had improved lameness.